Performance evaluation of a low-temperature solar Rankine cycle system utilizing R245fa - Wang, X.D.; Zhao, L.; Wang, J.L.; Zhang, W.Z.; Zhao, X.Z.; Wu, W. (Solar energy, 2010)
A low-temperature solar Rankine system utilizing R245fa as the working fluid is proposed and an experimental system is designed, constructed and tested. Both the evacuated solar collectors and the flat plate solar collectors are used in the experimental system, meanwhile, a rolling-piston R245fa expander is also mounted in the system. The new designed R245fa expander works stably in the experiment, with an average expansion power output of 1.73 kW and an average isentropic efficiency of 45.2%. The overall power generation efficiency estimated is 4.2%, when the evacuated solar collector is utilized in the system, and with the condition of flat plate solar collector, it is about 3.2%. The experimental results show that using R245fa as working fluid in the low-temperature solar power Rankine cycle system is feasible and the performance is acceptable.